TEACHERS’ PERCEPTION ON THE USE OF MOODLE APPLICATION IN ENGLISH AS FOREIGN LANGUAGE (EFL) ONLINE LEARNING - wati, Atikah; Prawiro, Indra Yoga; Maulida Nur Fauziah (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The aim of the current study is to explore teachers' perception of the use of Moodle applications in online learning of English as a foreign language (EFL).This is case study research with three English teachers in vocational high school 1 Indramayu as participants. They used Moodle applications in teaching online learning for three semesters. In order to obtain teachers’ perception of the use of the Moodle application in teaching online, interviews were used to gain the data, and it was analyzed qualitatively. The result showed that most teachers had a positive perception towards using the Moodle application in teaching online learning. It helped the teachers to be more creative in delivering the materials because many options or menus can be used. It also makes the teachers more active in using technology. The teachers also agreed that online learning, especially Moodle application, was important for students. The students can easily access any resource to support the material from the teachers. The school and teachers can also monitor and control students’ activities during the teaching-learning process. However, for further research, it is suggested to investigate other different applications that are used by teachers in the teaching and learning process, whether it is online or offline.